Impact of Product Placement in Entertainment Media of Nepal - Paudel, Aayush; Rawat, Ramesh (Nepalese Journal of Business, 2025)
This study examines the impact of product placement in entertainment media of Nepal. Consumer purchase intention is the dependent variable. The selected independent variables are product visibility, cultural relevance, audience familiarity, celebrity endorsement, brand recognition, and perceived authenticity. The primary source of data is used to assess the opinions of respondents regarding product visibility, cultural relevance, audience familiarity, celebrity endorsement, brand recognition, perceived authenticity, and consumer purchase intention. The study is based on primary data of 125 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of product placement in entertainment media of Nepal. The study showed a positive impact of product visibility on consumer purchase intention. It indicates that better product visibility leads to increase in consumer purchase intention. Similarly, the study showed a positive impact of cultural relevance on consumer purchase intention. It indicates that more cultural relevance leads to increase in consumer purchase intention. Likewise, the study also revealed a positive impact of audience familiarity on consumer purchase intention. It indicates that better audience familiarity leads to increase in consumer purchase intention. Further, the study observed a positive impact of celebrity endorsement on consumer purchase intention. It indicates that more celebrity branding or celebrity advertising leads to increase in consumer purchase intention. In addition, the study observed a positive impact of brand recognition on consumer purchase intention. It indicates that higher the brand recognition, higher would be the consumer purchase intention. Moreover, the study showed a positive impact of perceived authenticity on consumer purchase intention. It indicates that better perceived authenticity leads to increase in consumer purchase intention.